2009
DOI: 10.1002/cbic.200800595
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Environment Drives Selectivity for Sulfide Oxidation by an Artificial Metalloenzyme

Abstract: MAGIC Mn-salen mETALLOZYME: The design of an original, artificial, inorganic, complex-protein adduct, has led to a better understanding of the synergistic effects of both partners. The exclusive formation of sulfoxides by the hybrid biocatalyst, as opposed to sulfone in the case of the free inorganic complex, highlights the modulating role of the inorganic-complex-binding site in the protein. Artificial metalloenzymes based on the incorporation of Mn-salen complexes into human serum albumin display high effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…Purification of NikA and synthesis of ''NikA-metal complex'' hybrids Complexes 1-6 were synthesized as previously described [13,16,17]. Cytoplasmic apoNikA was overproduced and purified as already reported [12].…”
Section: Methodsmentioning
confidence: 99%
“…Purification of NikA and synthesis of ''NikA-metal complex'' hybrids Complexes 1-6 were synthesized as previously described [13,16,17]. Cytoplasmic apoNikA was overproduced and purified as already reported [12].…”
Section: Methodsmentioning
confidence: 99%
“…572 The Mn(III)–salen complexes used are shown in Scheme 13. Binding studies showed that the presence of charged R-groups could improve the binding affinity at pH 7.0, leading to more stable Mn(III)–salen⊂HSA hybrid proteins.…”
Section: Protein Redesignmentioning
confidence: 99%
“…The catalyst:thioanisole:H 2 O 2 stoichiometric ratio was 1:1000:100, and the oxidant was delivered over 45 min by syringe pump. Interestingly, the unique product detected was phenylmethylsulfoxide, which is likely related to the large substrate/oxidant ratio 18. Figure 6 shows the product formation as a function of time for both 1 ⊂BLG and the model complex [(L 5 2 )Fe II Cl] + .…”
Section: Resultsmentioning
confidence: 99%